Implementasi Strategi Konten Digital pada Platform Edukasi Investasi untuk Meningkatkan Literasi Keuangan melalui Magang Mahasiswa - Anita Anjani; M. Jumaedi (Jurnal Bersama Pengabdian Kepada Masyarakat (SAMAMAS), 2026)
The rapid development of digital technology has transformed the way people access financial and investment information. This condition creates opportunities for investment education platforms to reach a broader audience through digital media. This community service activity was conducted through an internship program at Sahaminaja, an investment education platform focusing on the dissemination of capital market information through various digital channels. The objective of this program was to support the improvement of public financial literacy through the implementation of digital content strategies while providing practical experience for students in communication and investment education. The implementation method employed a participatory approach through direct involvement in the company’s operational activities, including the management of WhatsApp Business and Telegram communications, the production of stock-related entertainment and educational content, the preparation of short educational video scripts, community engagement on the X platform, and the compilation of stock recommendation recaps and market research. The results indicate that digital media utilization supports wider dissemination of investment information, enhances audience engagement, and strengthens the quality of educational content delivered to the public. In addition to benefiting the company by expanding the reach of investment education, the program also provided valuable practical experience for students in applying academic knowledge within a professional working environment. The internship-based community service model, which integrates students into the operations of a digital financial education platform, demonstrates potential as an effective and sustainable strategy for improving public financial literacy in the digital era.